Relative effectiveness and cost-effectiveness of the midwifery-led care in Nova Scotia, Canada: A retrospective, cohort study. (October 2019) - Koto, Prosper S.; Fahey, John; Meier, Daniela; LeDrew, Michelle; Loring, Sally
Abstract: Objectives: To compare neonatal and maternal outcomes, and the relative risk of interventions between mothers attended to by midwives, general practitioners, and obstetricians, and to assess the cost-effectiveness of the employee-model of midwifery-led care in Nova Scotia, Canada, when compared with general practitioners. Design, setting, and participants: The study was a retrospective cohort study involving routinely collected clinical and administrative data from all low-risk births from January 1 st, 2013 to December 31 st, 2017. There were 24, 662 observations. Measurements: Descriptive statistics were used to summarise the mother's socio-demographic characteristics. We used a nearest-neighbour matching estimator in assessing differences in outcomes, and generalized linear models in the estimation of the risks of interventions, adjusting for potential confounders. An analytic decision tree served as the vehicle for the cost-effectiveness analysis, assessed using the net monetary benefit approach. All health care resources utilized were measured and valued. Neonatal intensive care admissions avoided was the measure of outcome. We performed probabilistic sensitivity and subgroup analyses. Findings: Mothers attended to by midwives spent less time at the hospital during birth admissions, were less likely to have interventions, instrumental births, and more likely to have exclusive breastfeeding at discharge from birth admission. There were no differences in Apgar scores and neonatal intensive care unit admissions. The employee-model of midwifery-led care was found to be cost-effective. Key conclusions: The midwifery program is both effective and cost-effective for low-risk pregnancies Implications for practice: Increasing the number of midwives will increase access and represents value for money.